Acoustic Simulation’s Verification of WFI ATHENA Filterwheel Assembly - PILCH, Adam; KAMISIŃSKI, Tadeusz; RATAJ, Mirosław; POLAK, Szymon (Archives of Acoustics, 2017)
Ariane 5 rocket produces very high sound pressure levels during launch, what can influence structures located in the fairing. To reduce risk of damage, launch in vacuum conditions is preferred for noise sensitive instruments. In Wide Filed Imager (WFI) project, the main part of the filterwheel assembly is an extremely thin ( 240 nm) filter of large area (170 × 170 mm), very sensitive to noise and vibrations. The aim of this study was to verify numerical calculations results in anechoic measurements. The authors also checked the influence of WFI geometry and sound absorbing material position on sound pressure level (SPL) affecting the filter mounted inside the assembly. Finite element method (FEM) simulations were conducted in order to obtain noise levels in filter position during Ariane 5 rocket launch. The results will be used in designing of WFI filterwheel assembly and endurance of the filter during launch verification.